Intolerância Contra O Linguista No Discurso Do Senso Comum1 - Bessa, José Cezinaldo Rocha [UNESP] (My University, 2015)
By this work, we aim at analyzing and show manifestation of intolerance against linguistic scholar that are manifested through the discourse of common sense people. This work is supported by studies from Linguistics, language rules, media and prejudice according to propositions by Scherre (2005), Fiorin (2002), Bagno (2003, 2006, 2012), Faraco (2001, 2007) and Oliveira (2007). In what is related to prejudice and linguistic intolerance, such as pointed by Leite (2008), the analyzed corpus is formed by 157 comments published by readers in a blog by Reinaldo Azevedo, in the context of a polemical publication of a textbook named Por uma vida melhor. The results show that the intolerance posture against the linguistic scholar is a reality in our days. And it assumes a posture that goes from a inacceptable position from that professionals to a disqualification of the own picture of the professional linguist.
Non tolerance with scholar linguistic in common sense discourse
Keywords: Common sense; Discourse; Intolerance; Linguist; Media.